Effectiveness Of Coffee Residuals As Green Roof Media - Kudubudin, Amirul Al-Amin Mohamed (Universiti Sains Malaysia, 2022)
The rapid process of urbanization has led to a decline in water -permeable green areas. As earth is facing the climate crisis, green technology -based solutions are worth exploring. Green roof is one of the green technologies that widely applied because it can reduce building temperature, improve rainwater quality, and slow down the flow of rainwater among others. However, more research needed on the effectiveness of green roof, especially the application of certain materials as a its medium. Therefore, coffee grounds are selected as a material potentially increasing the effectiveness of green roof. There are four green roof models measuring 20cm x 20cm x 45cm were constructed for this study involving control column samples and coffee residual column samples. Observation and laboratory experiments were conducted for a period of eight days. From the experiments, the average percentage of removal for selected parameters was recorded by coffee residual which was 72% (Turbidity), and 43.9% (Total Phosphorus) while for Color and Total Nitrogen were observed to increase due to several factors including system instability and organic content in the media. Meanwhile, the pH value was observed to nearly neutral at 6.9. When compared to the National Water Quality Standards the average water class is in class II for the Turbidity and pH parameters while other parameters exceeding the threshold values. The findings of the study found that coffee grounds have effectiveness based on two parameters namely Turbidity and pH but require further and continuous study for other parameters.